2013
DOI: 10.7860/jcdr/2013/4718.3025
|View full text |Cite
|
Sign up to set email alerts
|

Polypoidal Lesions in the Nasal Cavity

Abstract: Introduction: Nasal polyps are polypoidal masses arising from mucous membranes of nose and paranasal sinuses. They are overgrowths of the mucosa that frequently accompany allergic rhinitis. They are freely movable and nontender. Aims and Objectives:The purpose of this study was to study the histopathologic spectrum of polypoidal lesions of the nasal cavity. Materials and Methods:The study comprised of 100 consecu tive cases of polypoidal lesions in the nasal cavity, received in the department of pathology. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…7 A similar figure of 9.2% of the non-neoplastic masses has been reported by Kumariet al 8 Eosinophilic angiocentric fibrosis (n=1, 6.4% of all non-neoplastic lesions) was the next frequent non-neoplastic lesion encountered ( Figure-2), represented by a single case having nasal obstruction with no response to local medication. On examination there was a firm mass in the left nasal cavity.…”
Section: 2supporting
confidence: 51%
“…7 A similar figure of 9.2% of the non-neoplastic masses has been reported by Kumariet al 8 Eosinophilic angiocentric fibrosis (n=1, 6.4% of all non-neoplastic lesions) was the next frequent non-neoplastic lesion encountered ( Figure-2), represented by a single case having nasal obstruction with no response to local medication. On examination there was a firm mass in the left nasal cavity.…”
Section: 2supporting
confidence: 51%
“…41.67% was the reported incidence in a similar study conducted by Modh SK et al 6 . Khan N et al 17 reported an incidence of 42.85% among benign lesions in this region.…”
Section: Discussionmentioning
confidence: 99%
“…In study by Kalpana Kumari et al [25] malignant tumours were seen in 50% of the neoplastic cases and majority were sinonasal undifferentiated carcinomas (41%).…”
Section: Discussionmentioning
confidence: 99%